The influence of genetic polymorphisms of CYP3A on the pharmacokinetic variation and clinical outcomes of tacrolimus in a cohort of patients / Mohd Rahimi Muda - Muda, Mohd Rahimi (2014)
The complexity of determining the variability in tacrolimus pharmacokinetics parameter among organ transplant patients and its narrow therapeutic window characteristics necessitates proper drug monitoring in order to ensure the level is maintained within therapeutic range. Many studies have reported that variability of tacrolimus pharmacokinetics was due to differential expression of drug metabolizing enzymes CYP3A4 and CYP3A5 encoded by CYP3A4 and CYP3A5 genes respectively. The aim of the study was to develop a genotyping method in detecting CYP3A4*18, CYP3A5*3 and CYP3A5*6 mutations as well as investigating any correlation of genotyping findings with the clinical and tacrolimus related pharmacokinetics data and to quantify enzyme expression through the relationship of CYP3A4 and CYP3A5 mRNA copy number with the patients’ genotypes. Five ml of blood were withdrawn from the 80 patients and the DNA was extracted, thus proceeded for genotyping of CYP3A4*18, CYP3A5*3 and CYP3A5*6 variants using two steps PCR technique. Absolute quantification was employed where the serial dilution of plasmid from cloned bacteria to generate a standard curve was done prior to real time PCR method. Nine of 80 patients were found to be heterozygous of CYP3A4*18 (11.25%). As result of CYP3A5*3 polymorphism, eight patients were found as homozygous wild type (10%), 31 patients were heterozygous (38.75%) and 41 patients were homozygous mutant (51.25%). No CYP3A5*6 mutation was observed in this study. Homozygous mutant was significantly associated with lowest requirement of tacrolimus dose and highest adjusted level per dose (P<0.01). There was no significant correlation between CYP3A4 and CYP3A5 mRNA copy number with the CYP3A4*18 and CYP3A5*3 genotypes respectively. Significant correlation between CYP3A5*3 genotypes with the doses has provided a reliable information in predicting the appropriate individual tacrolimus doses